PENINGKATAN HASIL PEMBELAJARAN IPAS MENGGUNKAN MODEL PROJECT BASED LEARNING DI KELAS V SDN LADANG TENGAH 1 KABUPATEN TAPANULI TENGAH SUMATERA UTARA - Sholihah Pasaribu, Wildatun; Mansurdin; Erita, Yeni; Arwin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of fifth-grade students in science learning, which is caused by the continued use of lecture-based learning models. This makes learning less effective and causes students to experience boredom during learning activities. This research aims to determine the increase in creativity and learning outcomes of fifth-grade students using the Project-Based Learning (PjBL) model in Science subject matter, specifically the topic “How is the Shape of My Indonesia” at SD Negeri Ladang Tengah 1, Tapanuli Tengah Regency, North Sumatra. The data analysis technique used is interaction with a classroom action research (PTK) approach, which is carried out in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. Data collection techniques used include tests, non-tests, and observation. The subjects in this study were 118 fifth-grade students, consisting of 58 males and 66 females. The learning outcomes in cycle I increased from an initial score of 76.88 to 77.72 in the first meeting of cycle I, reaching 82.30 in the second meeting of cycle I, and 90. In cycle II, with a completeness level of 91.5, categorized as very practical. In addition, the Project-Based Learning model has also proven effective in improving student learning outcomes in the material “How is the Shape of My Indonesia.” Based on the research results, it can be concluded that the Project-Based Learning model in Science learning in fifth grade of Elementary School is declared valid, practical, and effective for use in the learning process. Keywords: 8Project8Based8Learning (PjBL),8IPAS8School